Pelatihan Literasi Baca Tulis dan Numerasi dengan Pendekatan Kontekstual Berbasis Kearifan Lokal Bagi Calon Guru SD STKIP Biak - Nasri Indra Padang; Widelmina K. Demena; Imanuel Keys Obet Worumboi (Yayasan Literasi Sains Indonesia, 2025)
Literacy training activities in reading, writing, and numeracy as a confirmation solution in facing the challenges of the world of work. Especially in the field of global and competitive education that requires prospective teachers to have the ability (Higher Order Thinking Skills) and professionalism. This training was held face-to-face starting on May 21-23, 2025 in the Elementary School Teacher Education Study Program Classroom at the Biak Teacher Training and Education College Campus. Involving 5 literacy facilitators and numeracy and 39 students of the Elementary School Teacher Education Study Program as participants. This training aims to equip students with the principles and values ​​​​of becoming prospective teachers, understanding related to literacy materials based on local wisdom and the potential for innovative and creative teaching skills. This training method uses interactive lectures, demonstrations and simulations. The three-day activity included (1) an introduction to the urgency and components of literacy and numeracy materials, (2) studying core literacy and numeracy materials and teaching strategies, and (3) continuing discussion of literacy and numeracy teaching materials and strategies. Based on observations and surveys, the majority of students did not understand the role of a teacher's values ​​and principles, had minimal knowledge of literacy and numeracy, and lacked optimal teaching skills strategies. However, the output of this activity showed a significant increase in understanding, enthusiasm, and participation of PSGD students, especially during discussion sessions, demonstrations, and teaching simulations. This activity is expected to be the first step in fostering awareness and readiness of the younger generation to face global challenges adaptively and competitively and improve the quality of their values ​​as teachers. It also serves as a foundation for further training to be more optimal, intensive, and sustainable in supporting the work readiness of PGSD students.